The Wiley Blackwell companion to the sociology of families - Treas, Judith; Scott, Jacqueline L.; Richards, Martin, 1940 January 26- (Chichester, West Sussex, UK ; Malden, MA : Wiley Blackwell, 2014)
Unprecedented social changes are taking place that pose new challenges for families. The Wiley Blackwell Companion to the Sociology of Families brings together a collection of original essays that investigate partnering, parenting, and families against the backdrop of rapid social change brought about by globalization, contested cultural values, severe economic shocks, new technologies, and widespread rethinking of welfare state protection for families today.
Judith Treas is Professor of Sociology and Director of the Center for Demographic and Social Analysis at the University of California, Irvine, USA.
Jacqueline Scott is Professor of empirical Sociology in the Faculty of Human, Social and Political Science, and a Fellow of Queens' College, University of Cambridge, UK.
Martin Richards is Emeritus Professor of Family Research, Centre for Family Research, University of Cambridge, UK. --Book Jacket.
Includes index.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Families; Families -- Research; POLITICAL SCIENCE -- Public Policy -- Cultural Policy; SOCIAL SCIENCE -- Anthropology -- Cultural; SOCIAL SCIENCE -- Popular Culture; Families; Families -- Research; Electronic books